Analisis Keuntungan Usaha Gula Aren Di Desa Ranoiapo Kecamatan Ranoyapo - Tilaar, Prichilia Theresa; Mandei, Juliana Ruth; Laoh, Esry Olly Harryani (AGRI-SOSIOEKONOMI, 2023)
The purpose of this research is to analyze the profit of palm sugar business in Ranoiapo Village, Ranoyapo Subdistrict. The research was conducted for 2 months from June to July 2023 from the preparation to the preparation of the research report located in Ranoiapo Village, Ranoyapo Subdistrict. The research data sources are primary data and secondary data where primary data obtained from direct interviews with palm sugar entrepreneurs in Ranoiapo Village, Ranoyapo Subdistrict and secondary data from relevant agencies, books, journals, scientific papers and google scholar. The population in this study are residents who do palm sugar business in Ranoiapo Village, Ranoyapo Subdistrict with a total of 18 entrepreneurs. As for the sample in this study as much as 35 percent of the total population of palm sugar entrepreneurs then obtained as many as 6 entrepreneurs who were used as respondents sampling was taken by simple random sampling or simple random. The research data were analyzed using profit analysis. The results showed that the profit of palm sugar business in Ranoiapo Village, Ranoyapo Subdistrict, obtained a result of Rp568,470 per week with a total cost of IDR208.655 per week and a total revenue of IDR777.125 per week, from the results of this profit if calculated per month then get a total profit of IDR2.253.880 from this total palm sugar business is profitable but still below the provincial minimum wage (UMP) of North Sulawesi Province which amounted to IDR3.485.000 in 2023.